Analisis Kebutuhan Petani Terhadap Penggunaan Benih Kentang Bersertifikat di Provinsi Jambi - Kurniasih, Siti; Sari, Maya; Rosyani, Rosyani; Muchlis, Fuad; Zakiah, Zakiah (Jurnal MeA (Media Agribisnis), 2025)
This study aims to determine the needs of farmers for certified potato seeds, to determine the use of certified potato seeds, and to determine the relationship between farmers' needs and the use of certified potato seeds in Kayu Aro District, Kerinci Regency. The analysis methods used were descriptive analysis and chi-square test analysis with 2×2 contingency. The results showed that farmers' demand for certified potato seeds was high, with a percentage of 66.67% for existence, 61% for relatedness, and 72.2% for growth. Furthermore, the level of certified potato seed usage was relatively high, with a percentage of 72.2%. Meanwhile, the chi-square test results showed that there was a significant relationship between farmers' needs and the usage of certified potato seeds.